THE INFLUENCE OF BRAND IMAGE AND PRICE PRODUCT OF WINGS PROTECTOR MEDICAL MASK TO PURCHASE DECISION DURING THE COVID-19 PANDEMIC IN 2020-2021 - Sumidartini, Ai Nety; Kuswara, Kuswara; Wardhana, Wredha Adhi Yudha (Fakultas Ekonomi Universitas IBA, 2024)
The purpose of this study was to analyze the effect of brand image on purchasing decision (X1), the effect of product price on purchasing decision (X2), and the effect of brand image and product price on purchasing decision (Y). This study used a quantitative approach with the type of research in the form of a questionnaire. The sample of this study were consumers of Wings Protector medical masks in Cilincing, North Jakarta. The analysis of the data used SPSS 26 to test theory and variables with statistical data analysis. From the results of this study, it can be concluded that there was an effect from the brand image inherent in the community on purchasing decisions and affordable product price on purchasing decision. Both brand image variable and product price variable had a positive and significant effect on purchasing decision, this happened because there was an effect of brand image and product price on purchasing decision on consumers of Wings Protector medical masks in Cilincing, North Jakarta.